The word in psychotherapy: A hermeneutic phenomenological understanding of speech and life. (Phenomenology, Humanities and Sciences, 2024)
The rise of research on non-specific or common factors of change in psychotherapy, as well as research on the therapeutic alliance, set the tone and the path towards an attempt to understand the psychotherapeutic process in an empirically generic way, and in a more transversal way than achieved through segmented explanatory theories. Echoing this call, this article interprets this drift as a need to be able to approach psychotherapy from itself, in its transversal condition of being a properly human phenomenon. For this purpose, an attempt has been made to establish a dialogue with hermeneutic phenomenology, in search of comprehensive categories that allow its disclosure, seeking to respect the way in which it is genuinely donated. As a result of this dialogue, understanding human life from a dynamic ontology of the event or occurrence allows us to account for its mobility as well as speech in psychotherapy, as a way in which existence can find intimacy with itself. This ontological transformation allows a unitary structure, which opens the possibility of understanding language, experience and life, elements of this phenomenon, as one and only dimension of the human.
Keywords: Psychotherapy; Hermeneutical Phenomenology; Occurrence or event; Formal indication